DARI GEREJA KE PANGGUNG POLITIK: STUDI TENTANG KEKUASAAN PENATUA DALAM POLITIK LOKAL DI MINAHASA - Romel Malensang (Journal of Governance, 2016)
Abstract: This article discusses about the phenomenon of penatua as  the ruling elite in contemporary Minahasa. The research method used was case study with data collection process for five months (November 2014 - March 2015). The results of this study led to the conclusion that the political role of the Church in Minahasa especially, it is not solely done by the institution of the church itself.The church only becomes a power instrument of most elites embodied in the figure of penatua and then doubling their domination in the political sphere.Keywords: penatua, church, local politics, Minahasa